(3GdeSGFd hGdCLhHIs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3eSCdI ai GSe Gddg JYGdi eSCdI ai GdhUjI, eSCdI ai bhdg JYGdi (B(((3Efce heG JYHOhf ef Ohf Gddg MUH Lgfe(B)q) s
(3BNQgG (B:s
(3GfJgi ef GdeSGFd CHh eMeO Hf GdSjO QMeg Gddg s
(3Vef eLehY , JQJjHgG (B: 1s
(3QGLY eNWhW (B59-3-(3chjJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B268s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
Keywords: (3GddZIs